Impact of high glycaemic index food consumption in patients with type 2 diabetes mellitus: A narrative review - Haris, Muhammad Akbar; Naufal, Naufal; Hulu, Victor Trismanjaya; Sihotang, Widya Yanti (Buletin Kedokteran & Kesehatan Prima, 2025)
Consumption of foods with a high glycaemic index (GI) in patients with type 2 diabetes mellitus (T2DM) can negatively impact their glycaemic control. High-GI foods typically induce a rapid increase in blood glucose levels. This research aimed to identify the impact of high glycaemic index food consumption in individuals with T2DM. A narrative review methodology was employed. The inclusion criteria for this study were articles published in indexed journal databases (Google Scholar, ScienceDirect, Scopus Journal, PubMed, ProQuest) written in English, with cross-sectional and experimental designs. Nine articles published between 2008 and 2025 met the inclusion criteria. The findings of this review underscore the importance of understanding glycaemic index food consumption in patients with T2DM. Integrating low-GI foods into the diet of individuals with T2DM may represent a practical strategy for improving metabolic control and reducing the risk of hyperglycaemia. Improved glycaemic control, such as that achieved by consuming a very-low-carbohydrate, high-fat breakfast, substantially reduces postprandial (after-meal) glucose excursions, particularly in the morning, a period when individuals with type 2 diabetes frequently experience the highest blood glucose spikes. In conclusion, improved glycaemic control, such as that achieved by consuming a very-low-carbohydrate, high-fat breakfast, substantially reduces postprandial (after-meal) glucose excursions, particularly in the morning, a period when individuals with type 2 diabetes frequently experience the highest blood glucose spikes.